DETERMINASI DANA SYIRKAH TEMPORER TERHADAP BAGI HASIL PADA PT. BANK BRI SYARIAH - Nur Aisyah; Munardi Munardi (LPPM Universitas Malikussaleh – Indonesia, 2020)
This study aims to determine the effect of temporary Syirkah funds on profit-sharing rates at PT. Bank BRI Syariah. This study uses secondary data in the form of quarterly financial statements for 2012- 2018 accessed on www.bi.go.id and www.brisyariah.co.id. The data analysis method used is a simple linear regression method with the help of Eviews. The results of the study partially show that temporary Syirkah funds significantly influence profit-sharing rates at PT. BRI Syariah Bank.